Augmented BMP signaling in the neural crest inhibits nasal cartilage morphogenesis by inducing p53-mediated apoptosis - Hayano, Satoru (Development, 2015)
Bone morphogenetic protein (BMP) signaling plays many roles in skull morphogenesis. We have previously reported that enhanced BMP signaling through the BMP type IA receptor (BMPR1A) in cranial neural crest cells causes craniosynostosis during postnatal development. Additionally, we observed that 55% of Bmpr1a mutant mice show neonatal lethality characterized by a distended gastrointestinal tract. Here, we show that severely affected mutants exhibit defective nasal cartilage, failure of fusion between the nasal septum and the secondary palate, and higher levels of phosphorylated SMAD1 and SMAD5 in the nasal tissue. TUNEL demonstrated an increase in apoptosis in both condensing mesenchymal tissues and cartilage of the nasal region in mutants. The levels of p53 (TRP53) tumor suppressor protein were also increased in the same tissue. Injection of pifithrin-α, a chemical inhibitor of p53, into pregnant mice prevented neonatal lethality while concomitantly reducing apoptosis in nasal cartilage primordia, suggesting that enhanced BMP signaling induces p53-mediated apoptosis in the nasal cartilage. The expression of Bax and caspase 3, downstream targets of p53, was increased in the mutants; however, the p53 expression level was unchanged. It has been reported that MDM2 interacts with p53 to promote degradation. We found that the amount of MDM2-p53 complex was decreased in all mutants, and the most severely affected mutants had the largest decrease. Our previous finding that the BMP signaling component SMAD1 prevents MDM2-mediated p53 degradation coupled with our new data indicate that augmented BMP signaling induces p53-mediated apoptosis by prevention of p53 degradation in developing nasal cartilage. Thus, an appropriate level of BMP signaling is required for proper craniofacial morphogenesis.